Native Aquatic and Wetland Plants: Blue-Eyed Grass, Sisyrinchium angustifolium - Kimberly A. Moore; Luci E. Fisher; Carl J. Della Torre; Lyn A. Gettys (EDIS, 2016)
This 2-page fact sheet discusses the classification, description, habitat, propagation, and uses of blue-eyed grass, an aquatic perennial native to Florida. Written by Kimberly A. Moore, Luci E. Fisher, Carl J. Della Torre III, and Lyn A. Gettys, and published by the UF Department of Agronomy, December 2015.